Chemical composition of soil solution under eucalyptus plantation in Southern Brazil - Viera, Márcio; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
This study focuses on changes in the chemical composition of solutions during their transfer in the soil cultivated with hybrid of Eucalyptus urophylla x Eucalyptus globulus stand in southern Brazil. The chemical composition of soil solution was evaluated from January to December in 2010, when the plant was from 8.5 to 9.5 years-old. Ceramic lysimeters was installed in order to measure the chemical composition of the soil solution in two different depths (30 and 80 cm) with six repetitions. The lysimeters were connected to a vacuum pump, where in each four hours, during ten minutes, the solution was suctioned. The soil solutions were collected in glass bottles with 0.5 liters of capacity. Fortnightly the samples were collected and each replicate of soil solution was analyzed separately. The solutions were filtered (0.45 μm) and the nutrients concentrations were measured. The concentration of N – NO3-, K+, Ca2+, Mg2+, Na+, S – SO42- and pH were variable during the year, but without significant difference (p > 0.05) in both depth (30 and 80 cm in depth). However, N - NH4+ concentration of soil solution was high, for both depths, in the months November and December. The concentrations of soil solution N – NO3-, N - NH4+, K+ and Mg2+ are not different in the soil profile (30 and 80 cm depth). S – SO42- (2.67 and 2.17 mg L-1, respectively in 30 and 80 cm depth) and Ca2+ (1.17 and 0.64 mg L-1, respectively in 30 and 80 cm depth) decrease in soil profile (p < 0.05), whilst, Na+ (2.10 and 2.60 mg L-1, respectively in 30 and 80 cm depth) and pH (4.78 and 5.11, respectively in 30 and 80 cm depth) increase in soil profile (p < 0.05). Pearson’s correlation between cations and anions in the soil solution was significant (p < 0.01). In both depths, N – NO3- was directly correlated with Ca2+ and Mg2+, whilst S – SO42- was inversely correlated with Mg2+. This change in chemical composition of soil solution indicated different patterns of nutrients were taken up by roots.